2021
DOI: 10.20892/j.issn.2095-3941.2021.0368
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes between immediate implant-based and autologous reconstruction: 15-year, single-center experience in a propensity score-matched Chinese cohort

Abstract: Objective: The number of immediate breast reconstruction (IBR) procedures has been increasing in China. This study aimed to investigate the oncological safety of IBR, and to compare the survival and surgical outcomes between implant-based and autologous reconstruction. Methods: Data from patients diagnosed with invasive breast cancer who underwent immediate total breast reconstruction between 2001 and 2016 were retrospectively reviewed. Long-term breast cancer-specific survival (BCSS), disease-free survival (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Although, clinically, no differences in oncological outcomes were reported when comparing patients receiving modified radical mastectomy (MRM) with patients undergoing MRM with immediate reconstruction ( 15 , 16 ), considerable debate exists whether complications following reconstruction may delay adjuvant therapies that can have a negative impact on oncologic outcomes. We have previously demonstrated no differences in oncological outcomes comparing implant-based and autologous breast reconstruction in a propensity score-matched setting ( 5 ). The present study expands on our previous work demonstrating factors that can compromise BCSS and DFS in patients who have undergone immediate reconstruction, and also allowed construction and validation of novel nomograms to predict individual BCSS and DFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, clinically, no differences in oncological outcomes were reported when comparing patients receiving modified radical mastectomy (MRM) with patients undergoing MRM with immediate reconstruction ( 15 , 16 ), considerable debate exists whether complications following reconstruction may delay adjuvant therapies that can have a negative impact on oncologic outcomes. We have previously demonstrated no differences in oncological outcomes comparing implant-based and autologous breast reconstruction in a propensity score-matched setting ( 5 ). The present study expands on our previous work demonstrating factors that can compromise BCSS and DFS in patients who have undergone immediate reconstruction, and also allowed construction and validation of novel nomograms to predict individual BCSS and DFS.…”
Section: Discussionmentioning
confidence: 99%
“…Although scientific studies posed oncological concerns that immediate reconstruction may change regional microenvironment, prolong surgical duration, delay the initiation of subsequent adjuvant therapy, and potentially lead to cancer recurrence, numerous clinical reports were published on the outcomes of immediate breast reconstruction following mastectomy and most supported its long-term oncological safety ( 2 4 ) compared to mastectomy alone. Our previous studies have demonstrated similar breast cancer-specific survival (BCSS) and local regional control between immediate implant-based and autologous breast reconstructions ( 5 ). The present study aims to investigate risk factors associated with the survival outcomes in breast cancer patients with invasive disease.…”
Section: Introductionmentioning
confidence: 99%